Effect of phototherapy on serum bilirubin and ionzed magnesium level in hyper- bilirubinemic neonates. - Khatri Sapkota, Niraj (Innovare Journal of Medical Sciences, 2017)
Background: Jaundice is a main problem in early neonatal period, it is suggested that there is a positive correlation between plasma ionized Mg levels and severity of hyperbilirubinemia in newborn. The aim of this study is to observe the effect of phototherapy on serum magnesium and biirubin level and explore the association evaluate it and interpret it's clinical significance in the cases of neonatal jaundice. Methods: A prospective study was conducted on 60 neonates in neonatology unit, Pediatrics Department, All of them suffering from neonatal jaundice > 6 - 20 mg/dl serum bilirubin level. Blood samples for determination of plasma Mg (total and ionized) and serum bilirubin levels were obtained from infants in 4 days, 6 days and 10 days and statistical analysis was conducted. Results: There was statistically significant difference in relation to ionized magnesium level before phototherapy Mean± SD(0.57±0.03mg/dl) and group after phototherapy Mean± SD 0.54±0.02 , P<0.05) correspondingly bilirubin level before phototherapy Mean± SD (13.9±3 mg/dl) and after phototherapy (9±3.4 mg/dl, P<0.05). Conclusion: From this prospective study, it is concluded that, Phototherapy decrease serum Mg level as it decreases serum bilirubin level and therefore there is a positive relation between serum bilirubin and serum Mg levels and rising of magnesium during hypebilirubinemic may be a physiological compensatory mechanism that counter toxic effect of bilirubin. Key words: bilirubin,phototherapy,Ionized Magnesium level.